THE IMPLEMENTATION OF STEM-BASED LEARNING ON MATTER PRESSURE TO IMPROVE MOTIVATION AND STUDENTS LEARNING OUTCOMES - ALIFFATUL ULFA, SITI; WIDODO, WAHONO (PENSA E-JURNAL: PENDIDIKAN SAINS, 2019)
The purpose of this research is to describe the motivation and student learning outcomes after implementing STEM-based learning. This type of the research is Pre experimental design and uses the One group pretest-posttest research design. The research was conducted at SMPN 17 Surabaya in class VIII-A and VIII-B. Increased motivation and student learning outcomes were analyzed using the N-Gain Score test. Student learning motivation has increased after STEM-based learning with an average N-Gain of 0.6 in each class with a medium category. Student learning outcomes have increased in each class and the N-Gain score is 0.7 with a high category. Based on these data it is stated that there is a consistent increase in student motivation and students learning outcomes after STEM-based learning is applied.